1999
DOI: 10.1007/bf02376014
|View full text |Cite
|
Sign up to set email alerts
|

Direct coal gasification with simultaneous production of electricity in a novel fused metal anode SOFC: a theoretical approach

Abstract: Abstract. Coal gasification in molten metal baths is a relatively new process with important technological advantages. The economics of the process can be made even more attractive if part of the Gibbs energy change of the oxidation reaction is directly converted into electricity through the use of the concept of a solid oxide fuel cell. This combination of fuel cell and fused metal gasifier in a single reactor-cell of the type: C, 02, fused metal / YSZ / perovskite, 02 is the distinguishing feature of the new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In addition, the liquid anode presents other suitable features: (i) the carbon active area can be effectively increased, by turning the solid electrode/solid carbon into a liquid electrode/solid carbon contact [8,9]; (ii) as the liquid metal is electronically conductive, the electrochemical reaction can be performed at the entire electrolyte/liquid metal interface; (iii) the molten metal, as an energy storage medium, can operate for a short period of time without fuels, in the battery mode, minimizing the negative effect of discontinuous fuel delivery [8]. First, Yentekakis et al [11,12] reported the gasification of coal with the simultaneous generation of electricity in an SOFC with a molten iron anode, an yttria-stabilized zirconia (YSZ) electrolyte immersed in the molten anode, and a Pt [11] or a perovskite [12] cathode, with carbon particles dispersed in the molten iron. A mathematical model was developed, describing the steady-state behavior of this fuel cell and the effect of operating conditions on cell performance.…”
Section: Liquid Metal Anode-direct Carbon Fuel Cells (Lma-dcfcs)mentioning
confidence: 99%
“…In addition, the liquid anode presents other suitable features: (i) the carbon active area can be effectively increased, by turning the solid electrode/solid carbon into a liquid electrode/solid carbon contact [8,9]; (ii) as the liquid metal is electronically conductive, the electrochemical reaction can be performed at the entire electrolyte/liquid metal interface; (iii) the molten metal, as an energy storage medium, can operate for a short period of time without fuels, in the battery mode, minimizing the negative effect of discontinuous fuel delivery [8]. First, Yentekakis et al [11,12] reported the gasification of coal with the simultaneous generation of electricity in an SOFC with a molten iron anode, an yttria-stabilized zirconia (YSZ) electrolyte immersed in the molten anode, and a Pt [11] or a perovskite [12] cathode, with carbon particles dispersed in the molten iron. A mathematical model was developed, describing the steady-state behavior of this fuel cell and the effect of operating conditions on cell performance.…”
Section: Liquid Metal Anode-direct Carbon Fuel Cells (Lma-dcfcs)mentioning
confidence: 99%
“…This was not the case for Pb and Sb, where the melting points of their metal oxides were lower than the operating temperature. Direct oxidation of coal has also been proposed to operate in a liquid iron anode SOFC [31].…”
Section: Other Metal Anodes For Lme Sofcsmentioning
confidence: 99%